Determining critical gaps in implementation of WHO and UNICEF’s 7-point plan in diarrhoea control and prevention strategy: A cross sectional study in District Swabi, Pakistan - Ibrahim, Muhammad; Azam, Naila; Riaz, Mehwish; Mahmood, Humaira; Tabassum, Farah; Rawail, Taharat (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the critical gaps in knowledge and practices of mothers/caregivers in the management of diarrhoea in children at home. Method: The descriptive cross-sectional study was conducted from September 2019 to August 2020 at primary health centres across Swabi district of the Khyber Pakhtunkhwa province of Pakistan, and comprised mothers/caregivers presenting with children aged <5 years suffering from diarrhoea. Barriers to childhood diarrhoea prevention and control were identified in accordance with the 7-point plan adopted by the federal government in 2009. Data was analysed using SPSS 23. Results: There were 287 mothers with a mean age of 26.8±5.39 years (range: 17-42 years). The mean age of the children was 24.85±12.72 months (range: 2-55 months). Among the mothers, 145 (51.5%) had received no schooling, 83(29%) had primary level schooling, 56(19.5%) secondary level and 3(1%) had received higher-level education. Only 63(22%) were aware of the use of oral rehydration salts and 32(11%) knew about the need of using zinc in diarrhoea. Safe water was available in 14(5%) households. Hand hygiene awareness was low, as 169(59%) mothers were washing hands with soap. Household access to toilet facility was 247(86%). Preventive health services were good with overall breastfeeding practices 204(71%) and children vaccination 244(85%.) Conclusion: Majority of mothers were found to be well aware of breastfeeding practices and the children had adequate vaccination coverage. There was a wide gap in direct awareness and practices of mothers about sanitation and hygiene and also home-based management of diarrhoeal diseases in children. Key Words: Diarrhoea, Sanitation and hygiene, Mothers, ORS, 7-point plan.